2018
DOI: 10.1016/j.cell.2018.06.014
|View full text |Cite
|
Sign up to set email alerts
|

Risk SNP-Mediated Promoter-Enhancer Switching Drives Prostate Cancer through lncRNA PCAT19

Abstract: The prostate cancer (PCa) risk-associated SNP rs11672691 is positively associated with aggressive disease at diagnosis. We showed that rs11672691 maps to the promoter of a short isoform of long noncoding RNA PCAT19 (PCAT19-short), which is in the third intron of the long isoform (PCAT19-long). The risk variant is associated with decreased and increased levels of PCAT19-short and PCAT19-long, respectively. Mechanistically, the risk SNP region is bifunctional with both promoter and enhancer activity. The risk va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
228
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 275 publications
(244 citation statements)
references
References 76 publications
(82 reference statements)
9
228
1
Order By: Relevance
“…LncSHGL could recruit HNRNPA1 to enhance translation of calmodulin mRNAs, which would activate the PI3K/Akt pathway and repressed the mTOR/SREBP‐1C pathway . Recently, it was reported that the convergence of HNRNPAB with lncRNA‐PCAT19‐long upregulated downstream cell‐cycle genes and promoted prostate cancer development and progression . This evokes the importance of characterizing the HNRNPAB‐lncRNA mechanism.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…LncSHGL could recruit HNRNPA1 to enhance translation of calmodulin mRNAs, which would activate the PI3K/Akt pathway and repressed the mTOR/SREBP‐1C pathway . Recently, it was reported that the convergence of HNRNPAB with lncRNA‐PCAT19‐long upregulated downstream cell‐cycle genes and promoted prostate cancer development and progression . This evokes the importance of characterizing the HNRNPAB‐lncRNA mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…29 Recently, it was reported that the convergence of HNRNPAB with lncRNA-PCAT19-long upregulated downstream cell-cycle genes and promoted prostate cancer development and progression. 30 This evokes the importance of characterizing the HNRNPAB-lncRNA mechanism. However, whether the hnRNP family directly regulates the expression of lncRNAs in cancer is not fully understood.…”
Section: Discussionmentioning
confidence: 99%
“…Taken together, these data provide evidence for functional contribution of rs2680700 in changing linc0597 expression or stability. However, the exact roles of these two SNPs in RA still need further exploration [45,46]. Additionally, we attempted to discover the correlations of H19 expression with their gene polymorphisms in RA patients, but still no statistically significant results were found.…”
Section: Discussionmentioning
confidence: 98%
“…Dao et al recently verified the functional mechanisms of Epromoters referred to as the promoters with enhancer functions, suggesting that regulatory elements with dual roles as transcriptional promoters and enhancers were strongly involved in cis regulation of distal gene expression in natural context [44]. Recently, the functional SNPs with both promoter and enhancer activities were reported [45], in which different alleles of a SNP mechanistically perform different functions. In our study, rs13239597 located in the promoter region of TNPO3 functions as an allele-specific functional enhancer, which highlights dual roles of its functionality.…”
Section: Discussionmentioning
confidence: 99%